Evaluation of using dietary supplements among polish adult people below and over 60 years of age - Katarzyna Suliga; Teresa Grzelak; Joanna Grupińska; Marta Pelczyńska; Marcelina Sperling; Krystyna Czyżewska (Journal of Medical Science, 2017)
Introduction. The population of elderly people is exposed to the development of disorders related to physiological ageing, as well as relatively common diseases occurring in the old age period. The gastrointestinal diseases, which reduce the absorption of many nutrients, are more frequent in the elderly compared to younger population. Material and Methods. In the study was attempted the assess of conditions of dietary supplementation by 60 years old people or older (60+). The comparisons of results were obtained with relation to young adults and middle aged persons (18–58 years). The survey was conducted with 368 adult, including 123 respondents over 60 years old and 245 younger people. Results. The study has been shown that dietary supplements were used by 64.2% of elderly people and 59.6% of younger respondents. The most common source of knowledge about dietary supplements in the elderly was a physician (40.7%) in contrast to younger population, where dominated the Internet (60.0%). The main reason of supplementation in the 60+ group was an enhancement the immune system, while in younger population it was important to improve the appearance of skin, hair and nails. The most common components of supplements, which were used in the elderly population, were vitamin C (32.5%) and magnesium (28.5%) compared to younger group where the most popular were vitamin D (22.5%) and magnesium (19.2%). Conclusions. The overuse of supplements, especially among the elderly, can lead to disability, therefore it is important to expand the education about side effects the improperly using of dietary supplements.